Thermal Aging Effect on the Joint Strength between an SOFC Glass-Ceramic Sealant and LSM-Coated Metallic Interconnect. (30th May 2017) - Hou, Fan-Lin; Lin, Chih-Kuang; Sugeta, Atsushi; Akebono, Hiroyuki; Wu, Si-Han; Yang, Peng; Lee, Ruey-Yi
Abstract : Lanthanum strontium manganite (LSM) has been practically coated on the metallic interconnect to prevent Cr poisoning in SOFC. The aim of this study is to investigate the joint strength between a glass-ceramic sealant and an LSM-coated interconnect steel at room temperature (RT) and 800 °C. Effect of long-term thermal aging is also characterized. Results indicate that LSM-coated specimens have a lower joint strength than the uncoated ones. It is attributable to the existence of pores around the interface between glass-ceramic sealant and LSM coating. However, the shear strength of LSM-coated joint specimen is enhanced by 52% at RT and by 200% at 800 °C after 1000-h thermal aging at 800 °C. The given thermal aging treatment also improves the tensile strength of LSM-coated joint specimen by 50% at 800 °C. It is attributed to a self-healing effect of the glass-ceramic sealant during thermal aging to reduce the pore size.